Formulasi Sediaan Sabun Wajah Minyak Atsiri Kayu Manis(Cinnamomum burmanni Nees Ex. Bl.) DanUji Aktivitas Antibakteri TerhadapStaphylococcus epidermidis - Nur Pramesti, Annindyta, Dr. T.N. Saifullah S, M.Si., Apt, Rima Munawaroh, M.Sc., Apt (2017)
Essential oil of cinnamon (Cinnamomum burmanni) containing sinamaldehid and eugenol has benefit as antibacterial. The essential oil is formulated in the form of facial soap to simplify the application. The facial soap of cinnamon essential oil can be used to prevent acne caused by the bacterium of Staphylococcus epidermidis. The purpose of this study was to determine the effect of cocamidopropyl betaine and glycerin usage on the physical properties and the physical stability of facial soap dosage and the antibacterial activity of Staphylococcus epidermidis. The formula facial of facial soap was made with a composition ratio of cocamidopropyl betaine and glycerin at Formula 1 (7:3), Formula 2 (6:4), Formula 3 (5:5), Formula 4 (4:6) and Formula 5 (3:7). The concentration of cinnamon essential oil used was 4%v/v. The test of the facial soap physical properties consits of pH, viscosity, foam height, specific gravity and alkali-free levels. The physical stability was tested by using the freeze thaw cycling. The bacterial activity was tested by using the pitting diffusion method. The research results of the physical properties test indicated an increaseon the composition of glycerine causing an increase of viscosity and an specific gravity. The results of physical stability test with the freeze thaw cyclingindicated a not significant decline (p-value> 0.05). The dosage of cinnamon essential oil facial soap indicated a decrease in the diameter of inhibitory zone after the freeze thaw cycling.